Analysis Pediatric Brain Anatomy and Motion Artifacts Between T2 TSE And T2 TSE Fast Blade Sagittal MRI 3T - Umi Rahmayanti LS; Hernastiti Sedya Utami; Arga Pratama Rahardian; Mochamad Syafi'ie; Pradana Nur Oviyanti (Green Publisher Indonesia, 2025)
Pediatric brain MRI is vulnerable to patients’ movement due to discomfort, resulting in anxiety, and may increase artifact susceptibility. Sedation is used to keep them calm during the MRI examination but it does not affect pulsation and flow artifacts. Fast acquisition technique and motion insensitive are required. Routine protocols of T2 sagittal pediatric brain MRI uses TSE sequences, but artifacts often appear on the image. BLADE fast imaging sequences are used with a pulse of MRI sequences, one of which is TSE with T2W. This research compared the image information of T2 TSE and T2 TSE fast BLADE sequences in pediatric brain MRI. It is a quantitative study with an experimental approach. The sample in this study was all pediatric Brain MRI examinations ≤5 years with the use of T2 TSE and T2 TSE fast BLADE sequences as many as 32 patients. Assessment of MRI image information was performed by 3 observers through visual grading analysis of sagittal brain anatomy image information and motion artifact, the data were analyzed using the Wilcoxon signed Rank Test. The results of the p-value statistical test showed that T2 TSE fast BLADE is significantly superior (p < 0.05) compared to T2 TSE in visualizing the overall anatomy and minimizing artifacts, image sharpness, lesion detection and diagnostic reliability of sagittal pediatric brain MRI. The conclusion T2 TSE fast BLADE sequence can be recommended in pediatric brain MRI examination because BLADE can eliminate all motion artifacts and produce optimal image information.